Valence shell electronically excited states of norbornadiene and quadricyclane - Cooper, Joseph C.; Holland, David M. P.; Ingle, Rebecca A.; Bonanomi, Matteo; Faccialà, Davide; De Oliveira, Nelson; Abid, Abdul R.; Bachmann, Julien; Bhattacharyya, Surjendu; Borne, Kurtis D.; Bosch, Michael; Centurion, Martin; et al. (Journal of Chemical Physics, 2024)
The absolute photoabsorption cross sections of norbornadiene (NBD) and quadricyclane (QC), two isomers with chemical formula C7H8 that are attracting much interest for solar energy storage applications, have been measured from threshold up to 10.8 eV using the Fourier transform spectrometer at the SOLEIL synchrotron radiation facility. The absorption spectrum of NBD exhibits some sharp structure associated with transitions into Rydberg states, superimposed on several broad bands attributable to valence excitations. Sharp structure, although less pronounced, also appears in the absorption spectrum of QC. Assignments have been proposed for some of the absorption bands using calculated vertical transition energies and oscillator strengths for the electronically excited states of NBD and QC. Natural transition orbitals indicate that some of the electronically excited states in NBD have a mixed Rydberg/valence character, whereas the first ten excited singlet states in QC are all predominantly Rydberg in the vertical region. In NBD, a comparison between the vibrational structure observed in the experimental 11B1–11A1 (3sa1 ← 5b1) band and that predicted by Franck–Condon and Herzberg–Teller modeling has necessitated a revision of the band origin and of the vibrational assignments proposed previously. Similar comparisons have encouraged a revision of the adiabatic first ionization energy of NBD. Simulations of the vibrational structure due to excitation from the 5b2 orbital in QC into 3p and 3d Rydberg states have allowed tentative assignments to be proposed for the complex structure observed in the absorption bands between ∼5.4 and 7.0 eV.<br
Keywords: Photoabsorption; Synchrotron radiation; Ions and properties; Isomerism; Absorption spectroscopy; Oscillator strengths; Organic compounds; Chemical compounds; Absorption band; Rydberg states